2017
DOI: 10.1021/acsphotonics.7b00626
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Graphene–Semiconducting Polymer Hybrid Photodetectors with Millisecond Response Time

Abstract: Graphene−semiconducting light absorber hybrid photodetectors have attracted increasing attention because of their ultrahigh photoconductive gain and superior sensitivity. However, most graphene-based hybrid photodetectors reported previously have shown a relatively long response time (on the order of seconds) caused by numerous long-lived traps in these hybrid systems, which greatly restricts device speed. In this work, graphene−thieno [3,4b]thiophene/benzodithiophene polymer hybrid photodetectors fabricated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Under the same device concept, graphene–polymer semiconductor (P3HT or PTB7) hybrid phototransistors (Figure c) have exhibited responsivity exceeding 10 4 A W −1 and the fast temporal response of ≈7.8 ms. In this device, the use of a SAM functionalization to effectively remove surface traps and charged impurities between graphene and SiO 2 substrate further improved responsivity up to 10 5 A W −1 (Figure d) . Tan et al demonstrated that the utilization of piezoelectric (PZT) substrate can improve the photocurrent of graphene–P3HT photodetectors by 10 times compared to that based on SiO 2 substrate due to the enhanced separation of photogenerated electrons and holes under the electric field of the polarization from the piezoelectric substrate .…”
Section: D‐based Photodetectorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Under the same device concept, graphene–polymer semiconductor (P3HT or PTB7) hybrid phototransistors (Figure c) have exhibited responsivity exceeding 10 4 A W −1 and the fast temporal response of ≈7.8 ms. In this device, the use of a SAM functionalization to effectively remove surface traps and charged impurities between graphene and SiO 2 substrate further improved responsivity up to 10 5 A W −1 (Figure d) . Tan et al demonstrated that the utilization of piezoelectric (PZT) substrate can improve the photocurrent of graphene–P3HT photodetectors by 10 times compared to that based on SiO 2 substrate due to the enhanced separation of photogenerated electrons and holes under the electric field of the polarization from the piezoelectric substrate .…”
Section: D‐based Photodetectorsmentioning
confidence: 95%
“…Copyright 2015, American Chemical Society. c,d) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: D‐based Photodetectorsmentioning
confidence: 99%
“…Device Fabrication : The SiO 2 layers with a thickness of ≈300 nm were first thermally grown on heavily doped p‐type Si wafers, and then the SiO 2 substrates were coated with ODTS SAMs following the process reported in the literature . The CVD‐grown graphene sheet on copper foil was transferred to the ODTS substrates using the traditional PMMA‐assisted method.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to organic molecules deposited under vacuum via the PVT method, solution‐processed organic molecules such as polymers, dye molecules, and biomolecules have been studied to facilitate device scalability as well as to achieve desirable properties . For example, a phototransistor based on the graphene/P3HT/poly[[4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐ b :4,5‐b′]dithiophene‐2,6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3,4‐ b ]thiophenediyl]] (PTB7) heterostructure has been developed for achieving high photoresponsivity of 10 5 A W −1 .…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%